Respostas fisiológicas e controle de Meloidogyne incognita em plantas de tomateiro tratadas com soluções ultradiluídas de Thuya occidentalis - Mioranza, Thaísa Muriel (2015)
The objective of this work was to study the influence of homeopathic or high diluted solution of Thuya occidentalis in the control of root-knot nematode Meloidogyne incognita in tomato plants and physiological responses promoted in the plant. The experiment consisted of in vitro and in vivo assay. The treatments were different dynamization of T. occidentalis 6, 12, 24, 50, 100, 200 and 400CH (centesimal hahnemaniana dilution) and the water (control). In the in vitro experiment nematodes were treated with 0.1% homeopathic solution of the treatments for 24 hours for the motility test and 15 days for hatching test. For the in vivo test, the experiment was carried out in two years, the first year in completely randomized design and the second year in a randomized block design, both with eight treatments and with four replications. At the moment that the tomato seedlings were transplanted, they were submerged in a 0.1% solution of treatments. Subsequently were inoculated 4188 eggs and 661 second-stage juveniles (J2) in the first experiment and 4350 eggs and 700 J2 in the second experiment. Were performed weekly sprays of 0.1% solution of the treatments in the shoots of plants. The plants were cultivated until the nematodes complete a development cycle. We evaluated the number of galls, egg masses, number of eggs and J2 in the roots, number of eggs and J2 in the soil, plant height, shoot fresh and dry weight, root volume, number of clusters, number of fruits per bunch, fresh and dry fruit weight and relative chlorophyll content. In the 2014 experiment were chosen the dynamizations 6, 24 and 50CH, and the control with nematode and treated with water and plants without nematodes and without treatment, with four repetitions each for the measurement of photosynthesis rates (A), stomatal conductance (gs), transpiration (E), internal CO2 concentration on leaf (Ci) and leaf temperature (Tleaf) varying the photosynthetic photon flux density (PPFD). It was also calculated the efficiency of water use (USA) (A/E), intrinsic water use efficiency (EUIA) (A/gs) and the instantaneous efficiency of carboxylation (A/C). The treatments did not show nematostatic and nematicide effect even did not influence in hatches eggs for in vitro assay. To the in vivo assay, in 2013, T. occidentalis 100CH caused a reduction in the population of J2 in the roots, as well as 200CH promoted an increase in the volume root and fruit fresh weight of the first bunch. In 2014, 100CH caused a decrease in the number of egg masses and J2 in the soil, and influenced the development of the root, while 50CH increased the fresh weight of shoots of tomato plants. The specific measures of gas exchange did not differ between treatments. Plants infected with M. incognita and without treatment caused an increase in the net photosynthesis and the carboxylation capacity for response curve to light. Already T. occidentalis 24CH inhibited the effect of increased CO2 fixation in tomato plants inoculated with M. incognita, providing similar behavior to healthy plants in different densities of photons. Plants of homeopathic treatments showed higher leaf temperature. T. occidentalis showed control capability of root-knot nematode and influenced in tomato growth and physiology